2016
DOI: 10.1126/science.aaf9070
|View full text |Cite
|
Sign up to set email alerts
|

Predictable convergence in hemoglobin function has unpredictable molecular underpinnings

Abstract: To investigate the predictability of genetic adaptation, we examined the molecular basis of convergence in hemoglobin function in comparisons involving 56 avian taxa that have contrasting altitudinal range limits. Convergent increases in hemoglobin-oxygen affinity were pervasive among high-altitude taxa, but few such changes were attributable to parallel amino acid substitutions at key residues. Thus, predictable changes in biochemical phenotype do not have a predictable molecular basis. Experiments involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
268
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(287 citation statements)
references
References 36 publications
17
268
1
1
Order By: Relevance
“…For example, birds typically express two main Hb isoforms in definitive red blood cells -a major isoform, HbA, which incorporates α-type products of the α A -globin gene, and a minor isoform, HbD, which incorporates α-type products of the α D -globin gene; the two isoforms share the same β-type subunits Grispo et al, 2012;Opazo et al, 2015). In all bird species that have been examined to date, the minor HbD isoform has an appreciably higher O 2 affinity than the major HbA isoform in the presence of allosteric effectors (Grispo et al, 2012;Projecto-Garcia et al, 2013;Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. Other sauropsid taxa also tend to co-express multiple, structurally distinct Hb isoforms in definitive erythrocytes (Weber and Jensen, 1988;Storz et al, 2011bStorz et al, , 2015bDamsgaard et al, 2013).…”
Section: Heterotropic Allosterymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, birds typically express two main Hb isoforms in definitive red blood cells -a major isoform, HbA, which incorporates α-type products of the α A -globin gene, and a minor isoform, HbD, which incorporates α-type products of the α D -globin gene; the two isoforms share the same β-type subunits Grispo et al, 2012;Opazo et al, 2015). In all bird species that have been examined to date, the minor HbD isoform has an appreciably higher O 2 affinity than the major HbA isoform in the presence of allosteric effectors (Grispo et al, 2012;Projecto-Garcia et al, 2013;Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. Other sauropsid taxa also tend to co-express multiple, structurally distinct Hb isoforms in definitive erythrocytes (Weber and Jensen, 1988;Storz et al, 2011bStorz et al, , 2015bDamsgaard et al, 2013).…”
Section: Heterotropic Allosterymentioning
confidence: 99%
“…5B). These taxa include ground doves, nightjars, hummingbirds, passerines and waterfowl Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. In the case of the passerines and waterfowl, we can make comparisons between closely related species as well as conspecific populations.…”
Section: Evaluating Evidence For An Empirical Generalization Regardinmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the best‐studied examples of genetically based adaptation involves the blood O 2 transport protein hemoglobin. Many organisms native to high altitude exhibit hemoglobin with a high affinity for oxygen (Weber, 2007); in birds, increased hemoglobin‐oxygen affinity has evolved convergently across multiple lineages occurring at high elevations (Natarajan et al., 2016). Studies of hemoglobin have also revealed environmentally induced phenotypic plasticity in response to pressures associated with high elevations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Na V 1.4-mediated TTX resistance, Hague et al (2017) suggest that permissible substitutions may be limited, as those that may be beneficial in terms of toxin resistance must also not disrupt the sodium channel's function. Recent molecular studies of functional convergence in the haemoglobin of high-altitude adapted bird species have also highlighted the importance of genetic background and the context-dependent effects of historic mutations (Natarajan et al 2016).…”
mentioning
confidence: 99%